Matrix metalloproteinase-9 regulates tumor cell invasion through cleavage of protease nexin-1. - Xu, D; McKee, C; Cao, Y; Ding, Y; Kessler, B; Muschel, R (2010)
Matrix metalloproteinase-9 (MMP-9) expression is known to enhance the invasion and metastasis of tumor cells. In previous work based on a proteomic screen, we identified the serpin protease nexin-1 (PN-1) as a potential target of MMP-9. Here, we show that PN-1 is a substrate for MMP-9 and establish a link between PN-1 degradation by MMP-9 and regulation of invasion. PN-1 levels increased in prostate carcinoma cells after downregulation of MMP-9 and in tissues of MMP-9-deficient mice, consistent with PN-1 degradation by MMP-9. We identified three MMP-9 cleavage sites in PN-1 and showed that mutations in those sites made PN-1 more resistant to MMP-9. Urokinase plasminogen activator (uPA) is inhibited by PN-1. MMP-9 augmented uPA activity in the medium of PC3-ML cells by degrading PN-1. Prostate cancer cells, overexpressing PN-1 or treated with MMP-9 shRNA, had reduced cell invasion in Matrigel. PN-1 siRNA restored uPA activity and the invasive capacity. PN-1 mutated in the serpin inhibitory domain, the reactive center loop, failed to inhibit uPA and to reduce Matrigel invasion. This study shows a novel molecular pathway in which MMP-9 regulates uPA activity and tumor cell invasion through cleavage of PN-1.